DETERMINANTS AND PATTERN OF HEALTH CARE SERVICES UTILISATION IN POST GRADUATE STUDENTS - Manzoor, Iram; Hashmi, Noreen Rahat; Mukhtar, Fatima (Journal of Ayub Medical College Abbottabad, 2009)
Background: The health care utilisation of a population is dependent on their health seeking behaviour which is determined by their physical, political, socio-economic and socio-cultural aspects. Objectives: This particular study is conducted to identify the determinants and the patterns of health services utilisation by the postgraduate students of Allama Iqbal Open University in Pakistan. It was a crosssectional study and conducted from December 2008 to April 2009 in Allama Iqbal Open University Islamabad. Methods: A non-probability convenience sampling was done in post graduate students who were enrolled for Masters Degree at Allama Iqbal Open University Islamabad. Data was collected on a self administered, pre-tested questionnaire to identify the pattern of utilisation of health care services by this educated class. Data was labelled and entered in SPSS version 16. Chi-square test is applied as a test of significance with fixing the p value at 0.05 as significant. Results: Only 129 students 32 males, 97 females) out of 250 responded to the questionnaire with the response rate of only 51.6%. The sociodemographic profile of the participants shows that 71 (55%) belong to age group 20-29 years, followed by 43 (33.3%) in age group 30-39 years. The marital status of the participants had a significant association with selection of health care services (p=0.04). Twenty-four (75%) of the males and 67 (65%) of the females were using private sector facilities. Age, marital status and income of the study subjects had significant association with selection of the provider with p values of 0.000, 0.047 and 0.051 respectively. Conclusion: The health care system in Pakistan comprises the public as well as private health facilities. In Pakistan vast majority of doctors resides in urban area and attracts the educated class towards private sector. Utilisation of public health care facility is not the main priority of the educated class of the country. Government officials should pay attention to make it more convenient for general public. Keywords: Utilisation, Health Care Services, Pakistan